O ondansetron, antagonista dos receptores 5-HT3, reverte o efeito ansiolítico das injeções de midazolam no hipocampo ventral de camundongos expostos aos modelos labirinto em cruz elevado (LCE) e exposição ao rato - Fachini, Gabriel (Universidade Federal de São Carlos, 2012)
Animal models have often been used to investigate the neurobiology of emotional states (fear and anxiety). In this sense, the elevated plus maze (EPM) and the rat exposure test are effective to evaluate these states and EPM exposure (aversive stimulus) can result in activation of serotonergic pathways with projections to structures belonging to the defense system, such as , amygdala, septum, hypothalamus, periaqueductal gray (PAG) and hippocampus. The hippocampus has a large amount of serotonin receptors (5- HT) and gamma-aminobutyric acid (GABA). In the present study, we used male mice of Swiss Albino, received surgical implantation of guide cannula and subsequent administration of drugs in the ventral hippocampus. After recovery, the animals were tested in EPM (Experiment 1 and 2) or the test exposure to the rat (Experiment 3 and 4). In Experiment 1, administration of midazolam (3.0 and 30.0 nmol) produced anxiolytic effect characterized by increased percentages of entries and time spent in the open arms of the EPM reduction measures and ethological (risk assessment) as percentages of dives stretched and secured. In Experiment 2, mice received combined injections Saline + Saline, Saline + MDZ, ondansetron (OND) + Saline and MDZ (30.0 nmol) + OND (0.03 nmol, antagonist of 5-HT3). Combined treatment of Sal + MDZ produced anxiolytic effect and this effect was reversed by the combined administration of OND + MDZ. The porcentanges of entries and time spent in open arms were lower (P> 0.05) than those found in group Sal + MDZ. Experiment 3 showed the effects of exposure of mice in the presence of mouse toy (RB = neutral stimulus) or mouse real (VR = aversive stimulus, Long Evans rats), under the administration of midazolam (3.0 14 and 30.0nmol). The animals were exposed to RV shortening the holding box (model effect) compared to animals exposed to RB. Animals treated with MDZ in two doses, there was an increase in transitions between the sides of the apparatus, increased time in the area of operation and increases the latency of escape to the protected area and contact time with the grid. In Experiment 4, we evaluated the effect of combined injection of midazolam and ondansetron protocol (Experiment 2). The MDZ 30.0 nmol produced anxiolytic effects and the blockade of this effect when the mice were combined administration of ondansetron and midazolam in the ventral hippocampus. Data from this study suggest that, first, control over emotional reactions and defense of the ventral hippocampus of mice exposed to EPM test or exposure to the rat are mediated via GABABenzodiazepines. Furthermore, there is a likely cross-modulation between GABAergic interneurons and 5-HT3, for blocking 5-HT3 via ondansetron can decrease the GABA release.
Keywords: Neurociência; Ansiedade; Serotonina; GABA (Ácido Gama Amino Butírico); Camundongo; Hipocampo ventral; LCE; Teste de exposição ao rato; Ondansetron; Midazolam; 5-HT; Mice; Ventral hippocampus; EPM; Ondansetron; Midazolam; Predator exposure test; GABA; 5-HT; CIENCIAS BIOLOGICAS::FISIOLOGIA